International roles of the European Union - ZIĘBA, RYSZARD (Rocznik Integracji Europejskiej, 2012)
The European Union plays a few kind of international roles: economic, political and security, and civilisational ones. The economic roles are the following: the world leader of sustainable development and the pattern of successful and complex integration, the biggest shareholder of world trade, the supplier of biggest development aid, the donator of biggest humanitarian aid. The political and security roles are such as: the role of active diplomatic actor and the role of stabiliser of peace and international security. Moreover the EU plays the role of an attractive civilisational centre and promoter of European culture values. Above roles confirm the EU has growing significance and ambitions to became a complex and global international actor. To materialise them the EU must to overcome the financial crisis and to save the threatened Euro zone, what is the sine qua non condition to survive the EU as a subject.